Broad spectrum light-trapping ternary polymer solar cells based on self-assembled nano-ridged active layer. (1st March 2020) - Li, Chang; Tao, Jiayou; Zou, Zhijun; Liao, Gaohua; Li, Fen; Wang, Jifei; Sun, Xiaoxiang; Ni, Jian; Zhang, Jianjun
Graphical abstract: In this paper, we first report the PTB7-Th:PC70 BM:PC60 BM TPSCs whose active layer is capable of forming the self-assembled nano-ridged (SANR) structures, and the SANR-active layer coupled with the textured-ZnO is able to form the double ridge superimposed system with broad spectrum light trapping characteristic, offering a promising way for the efficiency enhancement of the devices. Highlights: Self-assembled nano-ridged (SANR) structures was observed in TPSCs. SANR can significantly enhances the light absorption of the active layer. SANR coupled with textured-ZnO is able to form double ridge superimposed system (DRSS). DRSS shows the characteristics of broad spectrum light trapping. TPSCs with DRSS gives a optimal PCE of 10.68%. Abstract: Ternary blend polymer solar cells (TPSCs) comprising one donor and two fullerene acceptors is efficient method for improving the power conversion efficiency ( PCE ). In this paper, the PTB7-Th-based TPSCs which is incorporating PC70 BM and PC60 BM as mixed acceptors are fabricated and investigated. Impressively, the remarkable self-assembled nano-ridged (SANR) structures are discovered in the active layer with the weight ratio of 50% PC60 BM in fullerenes. Thanks to the enlarged interface area, enhanced light absorption and balanced carrier transport, the PTB7-Th:PC70 BM:PC60 BM TPSCs with the SANR active layer gives an optimal PCE of 9.68%. In addition, it is worth emphasizing that by combining the textured-ZnO with the SANR active layer, a double ridge superimposed system (DRSS) with broad spectrum light trapping characteristic is constructed, which can further enhance the light absorption of the devices. Finally, benefiting from the further increase in short circuit current density ( Jsc ), the PTB7-Th:PC70 BM:PC60 BM TPSCs with the DRSS gives an optimal PCE of 10.68%. This work provides a feasible ternary strategy to increase the devices performances and is proved be a simple and efficient strategy for fabricating PTB7-Th:PC70 BM:PC60 BM TPSCs with SANR active layer.